Organophosphate poisoning in Ongole cattle in Sukamandi - Yulvian Sani; Indraningsih . (Jurnal Ilmu Ternak dan Veteriner, 2005)
An integrated farming system between rice and beef cattle was initiated in 2000 in Sukamandi, West Java. However, since 2002 some cattle were suffering from neurological and ophthamological signs, and some of them were found dead after consuming rice straws. Field studies showed that 6 out of 12 cattle were suffered from eye disorders such as blindness, corneal opacity and sereous lacrimation. Two of 6 cattle were severely affected. But, neurological signs were not found during field observation. Pesticide analysis in rice straws shows that both groups of pesticide, organochlorines (OP) and organophosphates (OP) were detected. Residues of OC were higher than OP as shown as 14.41 vs 2.84 ppm (before processing) for OC and 1.80 vs 0.0003 ppm (processed) for OP consisting aldrin, lindane, dieldrin, endosulfan and chlorpyrifos methyl. There was only OC detected in sera consisting lindane (0.6–37.6 ppb); heptachlor (0.03–4.4 ppb); and aldrin (0.8–20.4 ppb) with an average total of 21,4 ppb. The neurological and ophthalmological signs were suspected to be due to organophosphates (OPs) contaminated-rice straws and any other factors such as insufficient vitamin A, magnesium and calcium. Feed replacement with fresh grasses for two cattle reduced corneal changes. Similar symptoms were also reproduced in Wistar rats dosed intraperitoneally with chlorpyriphos methyl. Clinical signs included incoordination, cachexia, eye disorder and corneal opacity. Necropsy showed hepatic injury (hepatic necrosis, mottling of hepatic surface and pale); pale kidneys; swollen of spleen and hyperaemic brain. Microscopic changes were found in brain, liver and eyes. Hepatic changes included haemorrhages, centrolobular hepatic necrosis and focal coagulative necrosis. Brains were showing focal necrosis, haemorrhages, vacuolisation, neuronal necrosis, chromatolysis and nucleolysis. Eyes appeared to have necrosis of tunica muscularis, haemorrhages and eosinophilic infiltration. The study indicates that organophosphates contamination in rice straws as animal feed may lead chronic neurological and ophthalmological symptoms.     Key Words: Contamination, Pathology, Organophosphates, Rice Straws, Cattle